Respuesta :

Answer:

The correct answer is B

Step-by-step explanation:

2(x-1) + 5x = x-8

Firstly, break all the brackets and you would got:

2x - 2 + 5x = x - 8

Put x into 1 side,

2x + 5x - x = -8 + 2

6x = -6

Divide both side by 6,

6x / 6 = -6/6

x = -1

The correct answer is B

Hope this help you :3

Answer:

The answer is -1 (B)

Step-by-step explanation:

Given the equation 2(x-1) + 5x = x-8.

To solve the equation for x;

Step 1: open up the bracket in the equation to have;

2x-2+5x = x-8

Step 2: bring all the terms on the right hand side to the left to have;

2x-2+5x-x+8 = 0

Step3: collect the like terms to have;

2x+5x-x-2+8 = 0

6x+6 =0

Step 4: subtract 6 from both sides to have;

6x+6-6 = 0-6

6x = -6

Step 5: divide both sides by the coefficient of x which is 6 to get x.

6x/6 = -6/6

x = -1

ACCESS MORE